2019
DOI: 10.3390/fermentation5030083
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol (DON) Accumulation and Nutrient Recovery in Black Soldier Fly Larvae (Hermetia illucens) Fed Wheat Infected with Fusarium spp.

Abstract: Fusarium head blight (FHB) is one of the most significant causes of economic loss in cereal crops, resulting in a loss of $50–300 million for Canadian agriculture. The infected grain (containing Fusarium-damaged kernels (FDKs)) is often both lower in quality and kernel weight, and it may be unsuitable for human and animal consumption due to mycotoxin presence. However, it still contains a considerable amount of nutrients. A method to recover the nutrients without the mycotoxins should be beneficial for the agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The fact that certain fungi can produce mycotoxins may cause safety problems for BSFL rearing. The fate of mycotoxins in substrates for BSFL rearing has already been a topic of research, for instance in references 44 47 , and is still under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that certain fungi can produce mycotoxins may cause safety problems for BSFL rearing. The fate of mycotoxins in substrates for BSFL rearing has already been a topic of research, for instance in references 44 47 , and is still under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when BSF larvae were reared on the experimental substrate spiked with heavy metals, Cd and Pb bioaccumulated in the BSF biomass, with the bioaccumulation factor (concentration in the organism divided by the concentration in the substrate) of 6.1-9.5 and 1.2-2.6, respectively, exceeding the statutory thresholds for animal feed (Purschke et al, 2017;Tschirner and Simon, 2015;van der Fels-Klerx et al, 2016b), while no bioaccumulation was observed for chromium (Cr), nickel (Ni), As, zinc (Zn), and mercury (Hg) (Diener et al, 2015;Purschke et al, 2017). Similarly, no bioaccumulation of mycotoxins (aflatoxins B1/B2/G2, deoxynivalenol, ochratoxin A, zearalenone) (Bosch et al, 2017;Camenzuli et al, 2018;Gulsunoglu et al, 2019;Lalander et al, 2016;Meijer et al, 2019;Purschke et al, 2017), pesticides (chlorpyrifos, chlorpyrifos-methyl, pirimiphos-methyl, azoxystrobin, propiconazole) (Bosch et al, 2017;Gulsunoglu et al, 2019;Lalander et al, 2016;Purschke et al, 2017), and pharmaceuticals (carbamazepine, roxithromycin, trimethoprim) (Lalander et al, 2016) have been observed in BSF biomass. The concentration of pesticides and pharmaceuticals decreased in the residual substrate, which was attributed to degradation of these compounds by microorganisms associated with BSF larvae.…”
Section: Microbial and Chemical Safety Of The Black Soldier Fly Bioma...mentioning
confidence: 93%
“…So far, no influence of exposure to mycotoxins, shown in Table 2, has been observed on larval growth performance or survival rate, probably due to limited accumulation of various mycotoxins, resulting in concentrations below the maximum/guidance values prescribed by the European feed law. In fact, the mycotoxin concentration in the residue (which is the remaining substrate along with excretion products of the BSFL) is in general even reduced compared to the substrate due to the presence of BSFL, except in one case of zearalenone (Bosch et al, 2017;Gulsunoglu et al, 2019;Leni et al, 2019;Purschke et al, 2017). Zearalenone can increase in the residue, possibly by the extractability of the compound.…”
Section: Mycotoxinsmentioning
confidence: 99%